Visual impairment and blindness among the students of blind schools in Allahabad and its vicinity: A causal assessment - Sushank Ashok Bhalerao (Indian Journal of Ophthalmology, 2015)
Background/Aims: Information on eye diseases in blind school children in Allahabad is rare and sketchy. A cross-sectional study was performed to identify causes of blindness (BL) in blind school children with an aim to gather information on ocular morbidity in the blind schools in Allahabad and in its vicinity. Study Design and Setting: A cross-sectional study was carried out in all the four blind schools in Allahabad and its vicinity. Materials and Methods: The students in the blind schools visited were included in the study and informed consents from parents were obtained. Relevant ocular history and basic ocular examinations were carried out on the students of the blind schools. Results: A total of 90 students were examined in four schools of the blind in Allahabad and in the vicinity. The main causes of severe visual impairment and BL in the better eye of students were microphthalmos (34.44%), corneal scar (22.23%), anophthalmos (14.45%), pseudophakia (6.67%), optic nerve atrophy (6.67%), buphthalmos/glaucoma (3.33%), cryptophthalmos (2.22%), staphyloma (2.22%), cataract (2.22%), retinal dystrophy (2.22%), aphakia (1.11%), coloboma (1.11%), retinal detachment (1.11%), etc. Of these, 22 (24.44%) students had preventable causes of BL and another 12 (13.33%) students had treatable causes of BL. Conclusion: It was found that hereditary diseases, corneal scar, glaucoma and cataract were the prominent causes of BL among the students of blind schools. Almost 38% of the students had preventable or treatable causes, indicating the need of genetical counseling and focused intervention.